Comparison Study on Cancel Culture as an Impact and Public Figure Scandal in Indonesia and Overseas - Miranda Putri, Vania; Octavia, Ivana; Tri Nuryanto, Hery; Nurhajati, Lestari (Institut Komunikasi dan Bisnis LSPR, 2024)
This research aims to comprehend the phenomenon known as